Acceptance for Social Health Insurance among Health Professionals in Government Hospitals, Mekelle City, North Ethiopia. (6th May 2020) - Tewele, Alemtsehay; Yitayal, Mezgebu; Kebede, Adane
Abstract : Background . Ethiopia is one of the countries with high out-of-pocket payments leading to catastrophic health expenditure. The government of Ethiopia introduced social health insurance (SHI) scheme with the overall objective of achieving universal health care access. Studying health professionals' acceptance to pay for social health insurance is crucial for the successful implementation of the scheme. Therefore, this study aimed to assess the acceptance of social health insurance and its associated factors among health professionals in government hospitals, Mekelle city, North Ethiopia. Methods . An institution-based cross-sectional study design was used. The study participants were selected using systematic random sampling. Data were collected using a structured interviewer-administered questionnaire and analyzed using SPSS version 20. Bivariable and multivariable logistic regression models at a 5% level of significance, and odds ratios with 95% CI level were used to determine the association between the health professionals' acceptance of health insurance and explanatory variables. Results . The study revealed that 62.5% of the respondents were willing to participate in the SHI scheme in which 74.9% were willing to pay 3% or more of their monthly salary. Health professionals' acceptance for SHI significantly associated with monthly salary (AOR = 9.49; 95% CI: 2.51, 35.86), awareness about SHI (AOR = 3.89; 95% CI: 1.05, 14.28), history of difficulty in covering medical bills (AOR = 6.2; 95% CI: 2.42, 15.87), attitudes towards social health insurance (AOR = 7.57; 95% CI: 3.14, 18.21), and perceived quality of health care services if SHI implemented (AOR = 2.89; 95% CI: 1.18, 7.07). Conclusion . The study indicated that there were still a high proportion of health professionals who were not willing to pay for SHI. Therefore, strengthening awareness creation, creating awareness about SHI, promoting the scheme using the different channels of communication to bring about favorable attitude, and providing health care services with required standard quality could help to increase the acceptance of SHI by health professionals.